Forming post-socialist urban identities through small-scale heritage-based regeneration: a role for intangibles?. Issue 5 (3rd September 2017) - Paskaleva, Krassimira; Cooper, Ian
Abstract: While the issue of socialist heritage in Central and Eastern Europe has been extensively researched by scholars, this paper addresses an existing gap in theory and practice ‒ how safeguarding socialist cultural heritage (tangible and intangible) can be used in post-socialist towns that have little emblematic resources available today to pursue urban progress and prosperity. The paper focuses on the city of Velenje in Slovenia and its collectivist means of original production. Attention is drawn to both the importance of this aspect of its intangible cultural heritage, and the problematic nature of appealing to it, to underpin citizens' engagement in a small-scale urban regeneration project. The paper offers insights about how using cultural heritage can be called upon to motivate citizens to participate in urban development and reform their urban identity, drawing on the recent past and living memory, through volunteered labour.